Minisatellite linkage maps in the mouse by cross-hybridization with human probes containing tandem repeats. - Julier, C (1990)
Tests of 29 human variable number of tandem repeat probes in inbred mouse lines showed that 80% (23/29) cross-hybridize, and 48% (14/29) produce multiple band, minisatellite polymorphisms (fingerprint patterns). Mini-satellite-type polymorphisms detected by 11 probes were characterized in eight different strains; on average, 240 polymorphic differences were detected between pairs of strains. Reproducible fingerprint patterns permit the study of the segregation of the minisatellite polymorphisms in experimentally designed crosses. As an example, we constructed primary minisatellite genetic linkage maps containing 346 polymorphic bands, distributed in 101 groups of closely linked systems, from genotypes on a recombinant inbred panel (C57BL/6J X DBA/2J); 38 of the groups were assigned by linkage to 15 autosomal chromosomes. The minisatellite genetic maps of C57BL/6J and DBA/2J can be applied in other linkage studies involving these strains.